Cinderella and the Lost Mice - Walt Disney Enterprises (Disney Princess Classic Library., 2012)
"It's winter in the kingdom, and Cinderella's mouse friends are cold! When the castle's mean housekeeper finds the mice warming up in Cinderella's room, she captures them and throws them out of the castle. Can Cinderella save her friends, or will someone else come to their rescue?"--Back cover.